Peran Media Sosial dalam Pembentukan Narasi Islam di Dunia Digital - Dermawan, Herman (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2024)
Social media has become a major platform for disseminating information and shaping public opinion in the digital era. This article explores how social media plays a role in shaping Islamic narratives, identifying the dynamics of message delivery, and its impact on the understanding and practice of religion among users. Using a qualitative approach, this study collected data through in-depth interviews and content analysis from various social media platforms. The results show that social media has great potential in disseminating diverse Islamic narratives, but also poses challenges related to the validity of information and extremism. This study concludes with recommendations for utilizing social media more effectively in the context of Islamic education and information dissemination.